TERAPI MUSIK UNTUK MENGURANGI KECEMASAN PADA IBU HAMIL TRIMESTER III - Debora Kote, Florensia; susanti, susanti (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2024)
Anxiety is often referred to as a condition where the emotional state cannot be controlled and managed well, causing a person's adrenaline to become restless and unfocused on something. A feeling of anxiety is different from a feeling of fear. Anxiety can be expressed by behavior or physiological changes which can cause several other uncontrolled symptoms and will affect a person's personality. Anxiety that lasts a long time and is not resolved quickly will give a bad impression to the welfare of the mother and fetus where there are several things that might happen, such as the mother's uterine contractions being too fast and not appropriate for the gestational age. The aim of this case study was to measure the level of anxiety felt by pregnant women in the third trimester by carrying out music therapy treatment for 7 minutes in 1 consecutive week at BPM Midwife Paulina, Batam City in 2024. The method of care is in the form of a case study. carried out on third trimester pregnant women with mild anxiety with music therapy and using documentation in the form of SOAP. The sample was 1 pregnant woman with mild anxiety at BPM Midwife Paulina. The assessment of maternal anxiety measures uses a questionnaire consisting of 14 questions regarding anxiety. After 1 week with an estimated time of 7 minutes of treatment, it was found that the mother's anxiety had disappeared and was no longer there.